Photostability of gold nanoparticles with different shapes: the role of Ag clusters - Attia, Yasser A. (2015)
Anisotropic gold nanostructures prepared by the seed method in the presence of Ag ions have been used to study their photostability to low-power UV irradiation (254 nm) at room temperature. It has been observed that, whereas spheres are very stable to photoirradiation, rods and prisms suffer from photocorrosion and finally dissolve completely with the production of Au(III) ions. Interpretation of these differences is based on the presence of semiconductor-like Ag clusters, adsorbed onto rods and prisms, able to photocorrode the Au nanoparticles, which are absent in the case of Au spheres. We further show direct evidence of the presence of Ag clusters in Au nanorods by XANES. These results confirm a previous hypothesis ( J. Am. Chem. Soc., 2014, 136, 1182–1185) about the major influence of very stable small Ag clusters, not only on the anisotropic formation of nanostructures but also on their photostability.